Estratégias químicas para controle de Conyza spp. e o efeito sobre a fauna edáfica - Ceresoli, Leocadio (2023)
This study aimed to evaluate different chemical treatments Conyza spp. control and the effect of these treatments on soil fauna. The experiment conducted in the municipality of Nova Prata do Iguaçu - PR in October and November 2020 and 2021. The experimental design conducted in randomized blocks, with 16 treatments and 4 replications. Three different doses of the herbicide EnlistDuo® Colex-D applied alone and associated with the herbicide Spider® 840WG in the first application, and sequential application with Finale® or Helmoquat®. Visual evaluations of percentage of control carried out at 7, 14, 21, 28, 35, 42 and 49 DAA in plants with 6, 5 and 4 mm stem diameter and the regrowth index at 35, 42 and 49 DAA. Treatment results were similar in both years. The treatments T15 (EnlistDuo® Colex-D (4,950 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Finale® (2,500 L ha-1)), T14 (EnlistDuo® Colex-D (4,130 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Finale® (2,500 L ha-1)) and T13 (EnlistDuo® Colex-D (3,300 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Finale® (2,500 L ha-1)), showed excellent control (93.50 to 97.00%) in plants with 6 and 5 mm stem diameter from 21 to 49 DAA. The T12 treatment (EnlistDuo® Colex-D (4,950 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Helmoquat® (2,500 L ha-1)), showed excellent control (95.00%) in plants with 5 mm from 21 to 49 DAA. Treatments T15, T14, T13, T12, T11 (EnlistDuo® Colex-D (4,130 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Helmoquat® (2,500 L ha-1)) and T10 ( EnlistDuo® Colex-D (3,300 L ha-1) + Spider® 840WG (42 g ha-1) + sequential Helmoquat® (2,500 L ha-1)) from 21 to 49 DAA showed excellent control (91.25 to 96.00%), in plants with 4 mm in both years. The treatments that presented better controls showed lower regrowth. The other treatments showed low control and a high regrowth rate in the evaluated period. The analysis of soil fauna carried out through the installation of Pitfall traps composed of plastic containers filled 1/3 of their volume with formaldehyde preservative solution (4%). The traps installed 7 days after the first application and after 7 days in the field, they taken to the soil laboratory at UTFPR Campus - Dois Vizinhos for processing and classification of soil fauna at the lowest possible taxonomic level. The 22 taxonomic groups sampled in the first assessment and 20 groups in the second. The data analyzed for the abundance of soil organisms and the ecological indices of Simpson's dominance, Shannon's diversity, Pielou's uniformity and Margalef's biodiversity. The abundance data analyzed and subjected to Principal Component Analysis (PCA). The most frequent organisms were Collembola, Acari, Formicidae, Nymph of Hemiptera, Diptera and Coleoptera. The treatments presented similar results and differed from the control in both years, showing no effect on the soil fauna.